Pollination by hoverflies in the Anthropocene. Issue 1927 (27th May 2020) - Doyle, Toby; Hawkes, Will L. S.; Massy, Richard; Powney, Gary D.; Menz, Myles H. M.; Wotton, Karl R.
Abstract : Pollinator declines, changes in land use and climate-induced shifts in phenology have the potential to seriously affect ecosystem function and food security by disrupting pollination services provided by insects. Much of the current research focuses on bees, or groups other insects together as 'non-bee pollinators', obscuring the relative contribution of this diverse group of organisms. Prominent among the 'non-bee pollinators' are the hoverflies, known to visit at least 72% of global food crops, which we estimate to be worth around US$300 billion per year, together with over 70% of animal pollinated wildflowers. In addition, hoverflies provide ecosystem functions not seen in bees, such as crop protection from pests, recycling of organic matter and long-distance pollen transfer. Migratory species, in particular, can be hugely abundant and unlike many insect pollinators, do not yet appear to be in serious decline. In this review, we contrast the roles of hoverflies and bees as pollinators, discuss the need for research and monitoring of different pollinator responses to anthropogenic change and examine emerging research into large populations of migratory hoverflies, the threats they face and how they might be used to improve sustainable agriculture.